2010
DOI: 10.1371/journal.ppat.1001114
|View full text |Cite
|
Sign up to set email alerts
|

CpG-Methylation Regulates a Class of Epstein-Barr Virus Promoters

Abstract: DNA methylation is the major modification of eukaryotic genomes and plays an essential role in mammalian gene regulation. In general, cytosine-phosphatidyl-guanosine (CpG)-methylated promoters are transcriptionally repressed and nuclear proteins such as MECP2, MBD1, MBD2, and MBD4 bind CpG-methylated DNA and contribute to epigenetic silencing. Methylation of viral DNA also regulates gene expression of Epstein-Barr virus (EBV), which is a model of herpes virus latency. In latently infected human B cells, the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(162 citation statements)
references
References 59 publications
9
149
1
Order By: Relevance
“…5A). The results indicated that viral transcription preferentially occurred from CpG-methylated virion template DNA as predicted (4). The ratio between DOXtreated meEBV-infected Daudi cells and wtEBV-infected cells without DOX corroborated this earlier finding at the level of individual genes, as can be seen with transcripts of four genes which were induced 400-to 500-fold (BRLF1, BMRF1), 350-fold (BcLF1), and more than 1,000-fold (BLLF1-gp220).…”
Section: Latently Infected Ebv-positive Akata Cells Support the Lytimentioning
confidence: 56%
See 2 more Smart Citations
“…5A). The results indicated that viral transcription preferentially occurred from CpG-methylated virion template DNA as predicted (4). The ratio between DOXtreated meEBV-infected Daudi cells and wtEBV-infected cells without DOX corroborated this earlier finding at the level of individual genes, as can be seen with transcripts of four genes which were induced 400-to 500-fold (BRLF1, BMRF1), 350-fold (BcLF1), and more than 1,000-fold (BLLF1-gp220).…”
Section: Latently Infected Ebv-positive Akata Cells Support the Lytimentioning
confidence: 56%
“…In general, herpesviral virion DNA is free of 5-methylcytosines, which is surprising in the case of EBV because its lytic DNA replication relies on highly CpG-methylated viral DNA in latently infected cells (4,26). In proliferating somatic cells, methylated cytosine residues are faithfully preserved during DNA replication and copied onto newly synthesized DNA strands, but our findings Daudi cells stably transfected with the DOX-regulated conditional expression plasmid iBZLF1 were infected with wtEBV and meEBV virus stocks for 2 days and incubated for two additional days with or without DOX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We wanted to investigate if VLP-derived BZLF1 transcripts regulate downstream genes and chose the BMRF1 gene as a representative example. This gene is prominently up-regulated early after infection (8) presumably because its promoter contains several BZLF1-responsive elements (43). EBV-negative Daudi cells with a BMRF1 promoter-driven luciferase gene served as reporter for the early expression of BZLF1.…”
Section: Resultsmentioning
confidence: 99%
“…Routes by which Zta activates gene expression have been documented for both viral and host promoters. Many promoters are targeted by the interaction of the sequence-specific DNA-binding domain of Zta with sequence-specific 7 nt DNA elements, termed ZREs (Adamson & Kenney, 1999;Bergbauer et al, 2010;Bhende et al, 2004Bhende et al, , 2005Broderick et al, 2009;Dickerson et al, 2009;Flower et al, 2011;Holley-Guthrie et al, 1990;Kalla et al, 2012Kalla et al, , 2010Karlsson et al, 2008;Kenney et al, 1989;Ramasubramanyan et al, 2012a, b;Sinclair, 2003;Sinclair et al, 1991;Woellmer et al, 2012). At least 32 distinct ZRE sequence variants are specifically recognized by Zta (Flower et al, 2011).…”
Section: Introductionmentioning
confidence: 99%